THE SIGNIFICANCE OF VICTIMOLOGICAL PREVENTION IN THE SYSTEM OF PREVENTION OF CRIMES - D.D. Dauletova (Journals Park Publishing, 2024)
The article presents a study of the concepts of victimology, victimization, victimoligical prevention, and also reveals the reasons for becoming a victim of crime. Analyzed the increased level of victimization in society, which is a weak preventive effect on the victimization of the population. Recommendations are given for preparing a system of victimological prevention measures.
Keywords: Crime, victimology, victimization, victims, victimoligical prevention.